線上文化回應教學成效探究：大專家教與原住民高中生之合作學習 Effects of Online Culturally Responsive Pedagogy: Collaborative Learning Between College Tutors and Indigenous High School Students - 林文川 Wen-Chuan Lin; 楊淑晴 Shu-Ching Yang (National Taiwan Normal University, 2015)
本文主旨在於探究英語學習歷程中，融入原住民文化資源的創新線上教學成效。根據Vygotsky 的學習理論，這項一年期的研究整合了線上學習與文化回應教學策略，以期激發原住民學生的英語學習動機。26 位來自臺灣南部的高中原住民學生與六位來自臺灣南部的大專英文系線上家教同時受邀參與研究。在兩個學期中，以每週1 小時，總計36小時的線上家教課程進行互動。第一學期焦點在於探究非同步互動概況；第二學期則聚焦於同步家教互動歷程以期回應原住民學生口語表徵的學習風格。本研究以質性研究方法為主，包含教室觀察、文件分析、反思筆記、田野筆記以及訪談。研究發現有兩方面；首先，能回應原住民學生學 習風格的線上同步文化回應家教，的確能激勵學生的英文學習。其次，大專家教學生認為線上英語教學的實踐以及與不同年齡學生之間，意義化的社會互動能增進他們個人的英語與跨文化溝通能力。本研究結果，有助於在結合線上學習與文化回應教學方面，理論與實務面向的應用；同時也能提供教育學者和政策制定者在思考如何提升原住民在校學習動機的具體參考。 This paper highlights the effects of implementing an innovative online pedagogy that accounts for indigenous students' cultural resources on the English-learning process. Based on Vygotsky's learning theories, this 1-year study combined online learning and culturally responsive teaching strategies in an attempt to motivate indigenous English language students. The study participants were 26 students from a class in an indigenous senior high school in Taiwan and 6 e-tutors who were English majors from a technological university in Southern Taiwan. A 1-hour online tutorial was conducted weekly for a total of 36 hours over two semesters. In the first semester, the study involved asynchronous interaction; synchronous tutorials were conducted in the second semester to culturally respond to the indigenous learning style of verbal representation. Qualitative methods included observing, documenting, maintaining reflection logs, fieldwork, and interviewing. The findings were twofold: the online synchronic tutorial successfully motivated the students, and the college e-tutors reported that English language practice and meaningful social interactions with cross-age peers improved their personal English learning motivation and cross-cultural competence. These findings may shed light on the theory and practice of combining online collaborative learning and culturally responsive teaching pedagogy. This insight may guide educators and policy makers aiming to enhance indigenous students' motivation to learn.